EVALUATION OF ALCOHOL RISK SCREENING AND INTERVENTION USING ALCOHOL USE DISORDERS IDENTIFICATION TEST-10 (AUDIT-10) IN KOTA KINABALU, SABAH - Norsyahida Md Taib; Mohd Shamril Mohd Nawi; Fredie Robinson; Syed Sharizman Syed Abdul Rahim (Universitas Airlangga, 2025)
Introduction: Alcohol consumption poses a significant public health concern due to its association with non-communicable diseases, social harm, and mental health issues. In Malaysia, the highest prevalence of alcohol consumption was in Sabah (28.6%) and Sarawak (31.2%), especially among indigenous and rural populations. Aims: This study aimed to examine demographic patterns linked to alcohol risk categories and evaluate the implementation of harm reduction interventions based on the Ministry of Health Malaysia’s 2013 community guideline. Methods: A retrospective cross-sectional study was conducted using secondary data from AUDIT-10 screenings collected between 1 January 2020 and 31 December 2024 in Kota Kinabalu, Sabah. Demographic variables included age, gender, ethnicity, and citizenship. categorised. Risk levels categorized AUDIT-10 scores, and associations with demographic factors were examined using chi-square tests. Intervention implementation was assessed based on documentation aligned with national guidelines. Results: Of the 1,066 records analyzed, males were significantly overrepresented in higher-risk categories χ² (3, N = 1066) = 51.14, p < 0.001). Indigenous groups formed the majority across all risk levels. While most participants were Malaysian citizens, non-citizens were more common in the low- and very-high-risk groups. Age distribution showed minimal variation across categories. However, incomplete records on intervention delivery limited the assessment of compliance with national protocols. Conclusion: The study underscores elevated alcohol risk among males and indigenous populations. Gaps in intervention delivery highlight the need for enhanced training and culturally tailored strategies. Strengthening data quality and implementation fidelity is crucial to improving alcohol harm reduction at the community level.